2017
DOI: 10.1002/iid3.142
|View full text |Cite
|
Sign up to set email alerts
|

Tumour cell conditioned medium reveals greater M2 skewing of macrophages in the absence of properdin

Abstract: IntroductionThe tumour microenvironment is shaped by the interaction of immune, non immune, and tumour cells present in close proximity. Tumour cells direct the development of a locally immune suppressed state, affecting the activity of anti tumour T cells and preparing the escape phase of tumour development. Macrophages in the tumour typically develop into so‐called tumour associated macrophages with a distinct profile of activities which lead to a reduction in inflammation and antigen presentation. The direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…These observations are similar to what has been observed previously with factor H ( 19 ), which is intriguing, since properdin and factor H have opposing effects on the regulation of complement activation ( 3 ). These findings were also consistent with previous reports, which have demonstrated that properdin deficient mice have a reduced M1 (IL-1β) and increased M2 (arginase-1, MCP-1, IL-10) profile, crucial for the tumor microenvironment ( 31 ). This suggests that the production of IL-1β and reduction in IL-10 mediated by properdin may be required for protection against M. tuberculosis in the initial phase of infection.…”
Section: Discussionsupporting
confidence: 93%
“…These observations are similar to what has been observed previously with factor H ( 19 ), which is intriguing, since properdin and factor H have opposing effects on the regulation of complement activation ( 3 ). These findings were also consistent with previous reports, which have demonstrated that properdin deficient mice have a reduced M1 (IL-1β) and increased M2 (arginase-1, MCP-1, IL-10) profile, crucial for the tumor microenvironment ( 31 ). This suggests that the production of IL-1β and reduction in IL-10 mediated by properdin may be required for protection against M. tuberculosis in the initial phase of infection.…”
Section: Discussionsupporting
confidence: 93%
“…Given a positive correlation with immune infiltration, the properdin expression levels reflect the presence of immune cells that are less immunosuppressive but can engage in the anti-tumor response. Another possibility is that properdin acts as a balancing factor between macrophage polarization between pro-inflammatory M1 and anti-inflammatory M2 phenotypes ( 30 ). NK cells, a key player in the anti-tumor immunity, have recently been shown to bind properdin through NKp46 receptor ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages derived from properdin knockout mice showed a shift to M2 phenotype, with increased type II cellular immune responses and decreased MHC class II expression (30). The lack of properdin has also been shown to protect the host from an aggravated inflammatory response, increasing the survival of properdin gene knock-out mice compared to wild type mice (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells thrive on an immunosuppressed microenvironment. To this effect, conditioned medium from melanoma B16F10 tumor cells has been shown to prime M1 macrophages, characterized by upregulation of iNOS, IL-1β, TNF-α, IL-12, IL-23, CXCL-9, and CXCL-10 ( 31 ). Thus, the tumor microenvironment could potentially be modulated by properdin-CNTs.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages of properdin-deficient mice have reduced M1 phenotype (IL-1β) and an increased production in the M2 phenotype (arginase-1, MCP-1, and IL-10) associated with tumour-promoting activity. This suggests that the deficiency in properdin can modulate macrophages toward an M2 phenotype, which enhances the tumor environment ( 31 ).…”
Section: Introductionmentioning
confidence: 99%